The differential collapse–filling evolution process of the paleo-underground river in the Northern Uplift of the Tarim Basin - Dong, Hong-Qi; Liang, Jia-Peng; Zhang, Qing-Yu; Li, Jing-Rui; Wan, Jun-Wei; Nie, Guo-Quan; Li, Yu-Lu (Frontiers in Earth Science, 2024)
The characteristics and stages of collapse–filling in paleo-underground rivers vary in recharge–runoff–discharge zones, constraining the associated fracture-caved reservoirs in carbonate strata. This paper comprehensively uses core, fluid inclusion, and carbon–oxygen isotope to probe the evolution process and migration of collapse–filling in paleo-underground rivers in the Northern Uplift of the Tarim Basin. The results show that 1) more than three stages of collapse–filling were identified in recharge–runoff–discharge zones, and a four-stage differential collapse–filling process was proposed to summarize the evolution of paleo-underground rivers. 2) The collapse–filling process varies spatiotemporally in the recharge, runoff, and discharge zones. Hydrodynamic strength and filling capacity migrate gradually from the recharge zone to the discharge zone. 3) Collapse–filling mechanisms, including gravity, suffusion, and suction–erosion mechanisms, also vary along with the collapse–filling evolution process of paleo-underground rivers. The research provided a new insight to recognize and interpret the differential planar distribution and vertical filling of the paleo-underground river system, which can be further applied to investigate the fracture-caved karst reservoirs.